Lost job, lost trust? On the effect of involuntary job loss on trust - Tim Friehe; Jan Marcus (Journal of Economic Psychology, 2021)
This paper tests the conjecture that involuntary job loss erodes trust. Using the German Socio-Economic Panel and considering how trust evolves over a quinquennial time interval, we find that job loss decreases trust by about 9 percent of a standard deviation.
Keywords: J24; J64; 330; Trust; Job loss; Unemployment; SOEP